Simulation Research on the Load Transfer Mechanism of Anchoring System in Soft and Hard Composite Rock Strata under Tensile Loading Conditions - Ning Li; Zhanguo Ma; Peng Gong; Fuzhou Qi; Tuo Wang; Shixing Cheng (Advances in Materials Science and Engineering)
Soft and hard composite rock strata are frequently encountered in transportation, geotechnical, and underground engineering. However, most of the current support is designed for homogeneous rock masses, which ignores the different anchoring effect in soft and hard composite rock strata. A numerical study is presented in this paper on the pull-out behavior of fully grouted rock bolts in soft and hard composite rock strata. The nonlinear bond-slip relationship of bolt-grout interface that is anchored in soft rock and hard rock is obtained from laboratory test, respectively. Then, the nonlinear bond-slip relationship is put into the numerical model. The numerical result shows a close match with the experiment tests and the proposed model. Lithological sequence, layer thickness ratio, and layer numbers are taken into consideration in numerical simulation models. Under the same layer number, the shallower-soft and deeper-hard composite rock strata (SHCRS) have a higher bearing capacity and deformation resistance than the shallower-hard and deeper-soft composite rock strata (HSCRS). As the soft-to-hard thickness ratio in SHCRS increases, the initial stiffness of the load-displacement curve and peak load decreases continuously. The load-displacement curve shows the same initial stiffness for different hard to soft thickness ratios in HSCRS. As the hard to soft thickness ratio increases, the load peak and the displacement at the peak load increase. Therefore, the closer the hard rock is to the loading end, the greater the initial stiffness of the load-displacement curve is. The greater the hard rock thickness, the larger the peak load. Under the same anchor length, the peak load and the displacement at the peak load decrease with the increase of layer numbers, but the reduction magnitude decreases. This paper leads to a better understanding of the load transfer mechanism for the anchoring system in soft and hard composite strata and provides a reference for scientific support design and evaluation method.